Conceptualising Supply Chain Management: An Objective-Oriented Approach - Alkebaisi, Hussain (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event 2018.Although it has been more than three decades since the concept of Supply Chain Management (SCM) was first introduced, there are still significant attempts at, and a call for conceptualising, defining, remodelling and identifying the theory(s) behind it. There is no consensus in the literature on a concise and precise definition of SCM nor its underpinning theory(s). A rigorous theoretical framework has not yet been developed; the existing models like Supply Chain Operations Reference (SCOR) and the Global Supply Chain Forum (GSCF) models lack the details called for in a holistic model that encompasses the essence of SCM and integrates the best features of the existing models and covers their shortcomings.The argument in the literature is that: “research and practice would be improved if a single definition were adopted” (Mentzer et al., 2001); “closing the gap between SCM theory and actual practice would be the development of a single, unifying SCM framework that both incorporates the best aspects of the existing, widely used frameworks and addresses their current limitations” (Moberg et al., 2008). However, in this research, the author argues that a consensus on a unified conceptual/theoretical framework of SCM will contribute to solving those theoretical issues.The literature has shown that most of the research approaches which were used to solve those theoretical issues were process-oriented or business functions-oriented, that is, the focus was on what firms and organisations are doing, where they do it, or how they do it. However, the main gap the researcher has identified through the study and the analysis of the literature is that an Objective-Oriented approach has not been investigated in resolving those theoretical issues. Also, the researcher found that the objectives of SCM and supply management as a whole were scattered in the literature. In this study, the researcher objective is to investigate the viability of using this approach in solving those theoretical issues.The researcher found that an appropriate research methodology to investigate the viability of an Objective-Oriented approach would be to apply the Grounded Theory research methodology, which is a well known qualitative research methodology that is used in developing theories or theoretical frameworks from data (grounded) through line-by-line coding and categorising process. Recent work reported by Randall and Mello, (2012) recommended the use of the Grounded Theory research methodology as they established that grounded theory “can be an appropriate tool for creating theory in supply chain research”. This methodology has also been recommended by Denk, Kaufmann and Carter, (2012) and Manuj and Pohlen, (2012)Therefore, this research focuses on the implementation of the Grounded Theory research methodology through an Objective-Oriented coding system that will analyse multiple data resources including the literature, websites, recorded lectures and recorded interviews. Through this approach, the researcher was able to: conceptualise SCM, identify the theory behind it, define the concept precisely and concisely and develop a unified model that visualises SCM.
Keywords: 'Supply chain management'; 'objective-oriented approach'; 'Grounded Theory Study'; 'grounded theory method'; 'CranfieldDN2018'; 'Logistics and Supply Chain Management'